Pengaruh Kualitas Prodakd Kualitas Pelayanan Terhadap Kepuasan Konsumen di Toko Kemenangan Kota Bima - Muhammad Afwan Riadin; Sri Ernawati; Ismunandar (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
This study aims to analyze the effect of product quality and service quality on customer satisfaction at Toko Kemenangan Kota Bima. The type of research used is causal associative with a quantitative approach. The population consists of all customers who have shopped at Toko Kemenangan Kota Bima, with an unknown total number (unknown population). The sampling technique used is accidental sampling, with a total of 65 respondents. The research instrument was a Likert scale questionnaire consisting of 13 indicators. Data analysis was carried out through validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, correlation coefficient, and determination coefficient.The results of the study show that: (1) Product quality has a positive and significant effect on customer satisfaction; (2) Service quality has a positive and significant effect on customer satisfaction; (3) Product quality and service quality simultaneously have a significant effect on customer satisfaction. The correlation coefficient value of 0.842 indicates a very strong relationship, while the determination coefficient value of 70.9% indicates that variations in customer satisfaction can be explained by product quality and service quality, while the remaining 29.1% is influenced by other factors outside the scope of this study.